Control of reaching movements in 6-year-old prematurely born children with motor problems -- an intervention study. - Eliasson A; Rösblad B; Häger-Ross C (Advances in Physiotherapy, 2003)
The aim was to improve the control of reaching movements in prematurely born children with impaired coordination. Fifteen 6-year-old prematurely born children (birth weight < 1500 g) practised mouse-controlled computer games daily for 4 weeks. In addition, as a control condition, each child practised trampoline jumping for an equally long period. The outcome was measured in terms of: (1) computer game skill, (2) kinematic analysis of planar reaching movements on a digitizing tablet, and (3) motor performance measured with the Movement ABC. After intervention, all the assessments used showed an improvement although only the skill in performing the computer game was clearly related to the type of intervention. Lack of tight correlation between computer game practice and performance on the digitizing tablet might be due to minor but crucial differences in control aspects between the tasks. The present results indicate that the expectation of transfer even to very similar tasks should be low. The findings thus support a task-specific approach to practice, while corroborating the positive impact of non-specific intervention.